Wu Tingfang (1842-1922) : Reform and Modernization in Modern Chinese History - Pomerantz-Zhang, Linda (Book collections on Project MUSE., 1992)
This book is a biography of Wu, and sheds considerable light on a crucial period in Chinese history.